Thermodynamic modelling of ultra-high vacuum thermal decomposition for lunar resource processing. (15th September 2021) - Shaw, Matthew G.; Brooks, Geoffrey A.; Rhamdhani, M. Akbar; Duffy, Alan R.; Pownceby, Mark I.
Abstract: This study presents a theoretical pathway to the production of sodium and potassium metal from lunar regolith at ambient lunar conditions via the selective thermal decomposition of oxides in the regolith using concentrated solar energy. The proposed process for the recovery of the products is systematically evaluated via thermodynamic modelling based on Gibbs energy minimalization using the FactSage software package. Initial modelling predicts that at ambient lunar pressures (10 −15 ​atm), and assuming equilibrium conditions, a thermal decomposition process run at 800 ​°C, followed by a fractional deposition sequence with stage temperatures of 550 ​°C and −50 ​°C can result in the concentration of FeO in the first deposition and Na and K metal in the second deposition. These results support the feasibility of a thermal decomposition process for the beneficiation and reduction of mineral resources on the lunar surface. Highlights: Lunar regolith processed at lower energy costs using the Moon's ambient conditions. Lunar ISRU via thermal decomposition with concentrated solar energy is proposed. Viability of concentrating FeO is thermodynamically demonstrated. Viability of Na and K Extraction is thermodynamically demonstrated.